Estimation of some Vibrational Spectroscopic Constants of Group V Trihalide - N., Jigeesh; M., Rangacharyulu (Malaysian Journal of Science, 2005)
From the available experimental reports on structural and vibrational spectroscopic data of group V trihalids, it was observed that the bond distances bear a linear relationship with their respective vapour phase vibrational frequencies and bond angles. A least squares fit was made between bond distances and bond angles on one hand and bond distances and vibrational frequencies on the other hand. Using this method, some unknown structural data and vapour phase vibrational frequencies of some molecules of group V trihalides for which the data is not so far available were estimated. From the experimental and estimated data, the molecular constants like force constants, coriolis coupling constants, centrifugal distortion constants and mean amplitudes of vibration have been evaluated.